Pteridophyte flora of Rampahar and Sitapahar reserve forests under Rangamati district in Bangladesh - Uddin, Sarder Nasir; Hassan, Md Abul (Dhaka University Journal of Biological Sciences, 2012)
A taxonomic survey was conducted to study pteridophyte flora of Rampahar and Sitapahar reserve forests under Rangamati district in Bangladesh. The survey was accompanied with collection of voucher specimens of the available pteridopyte species in the area and deposition at Bangladesh National Herbarium as reference material. The study found 41 pteridophyte species belonging to 26 genera under 13 families from the area. It constitutes 21 per cent of total fern flora of the country including one threatened species viz. Tectaria chattagramica (Clarke) Ching. DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11513 Dhaka Univ. J. Biol. Sci. 21(2): 153-161, 2012 (July)